Peningkatan Brand dan Product Value Pathilo - Oris Umbu Laki Nuga; Hamdan Anwari; Arif Dwi Saputra; Alfina Damayanti; Wafiroh; Noverinto Gilang (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2023)
Improving the Brand and Product Value of Pathilo The Community Self-Reliance Program through the Community Service Scheme is an activity initiated by the Sekolah Tinggi Pariwisata AMPTA Yogyakarta Institute of Tourism and Community Service, which is intended to provide assistance and training to increase the brand and product value of Pathilo' as locally processed products. The mentoring and training activities are expected to produce output and achievement from Pathilo Brand. Product Value Improvement activities in Pakel, Tepus, Gunungkidul is a manifestation of public awareness, especially Pathilo local product business owners, in branding products so that businessmen of small and medium enterprise have selling value for potential consumers Pathilo's processed products are wrong commodity for the local community and a choice of souvenirs for tourists visiting the Tepus Tourism Village. Even so, the interest and views of the broader community towards this refined product are mediocre. This is due to the need for branding of the product itself. In addition, the public and business actors have yet to utilize digital platforms for marketing, and there has been no innovation in these processed products, which makes the products look dull and unattractive. Therefore, this service activity aims to increase branding and create value from Pathilo products